Effects of Dimethyl Sulphoxide and of Vitamin A on Human Platelets - Davey, M. G; Lüscher, E. F (Thrombosis and Haemostasis, 1968)
Dimethyl sulphoxide (DMSO) causes some release of amino acids, adenine nucleotides, and acid phosphatase and β-glucuronidase activities from washed human platelets. Addition of vitamin A with DMSO greatly enhances the effect; but vitamin A in ethanol added to platelets fails to release amino acids and nucleotides. Release appears to be due to a change in permeability of the platelet membrane, not to the discharge of contents of intracellular structures. Lipid peroxidation of membrane phospholipids, or a similar reaction, may be involved. Thrombin causes a different type of alteration in platelet permeability.The results suggest that DMSO should not be used as a preservative for platelets. They may have some bearing on the mechanisms of toxicity of DMSO and vitamin A.